Effects of Broad-Spectrum Antimycobacterial Therapy on Chronic Pulmonary Sarcoidosis - Drake, Wonder; Richmond, B. W.; Oswald-Richter, K.; Yu, C.; Isom, J. M.; Worrell, J. A.; Shipl, R. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
BackgroundSarcoidosis is an idiopathic, granulomatous disease for which molecular and immunologic studies  have shown an association between it and mycobacterial antigens.  Microbial antigens can reduce expression of the tyrosine kinase Lck, which has been associated with sarcoidosis severity.  Here we investigate the efficacy of Concomitant Levofloxacin, Ethambutol, Azithromycin, and Rifampin (the CLEAR regimen) for treatment of chronic, pulmonary sarcoidosis.MethodsFifteen chronic, pulmonary sarcoidosis patients with forced vital capacities (FVC) between 45-80% of predicted were enrolled in this open-label trial.  The primary efficacy endpoint was change in absolute FVC from baseline to completion of therapy.  Secondary endpoints were change in functional capacity measured by Six Minute Walk Distance (6MWD) and quality of life assessment measured by St. George’s Respiratory Questionnaire (SGRQ).ResultsOf 15 patients enrolled, 11 completed 4 weeks of therapy, and 8 completed 8 weeks of therapy.  The CLEAR regimen was associated with an increase in FVC of 0.23 liters at 4 weeks and 0.42 liters at 8 weeks (P=0.0098 and 0.016, respectively).  The 6MWD increased by 87 meters from baseline to 8 weeks (p=0.0078).  The mean score of the validated SGRQ was improved at 8 weeks over baseline (p=0.023).  Normalized expression of Lck and NF-κB was observed in those with clinical improvement.ConclusionsThe CLEAR regimen is associated with improved absolute FVC, as well as increased functional capacity and quality-of-life in selected chronic pulmonary sarcoidosis patients.  Larger, randomized, controlled trials are needed to confirm these findings and to identify patients most likely to benefit from therapy. ClinicalTrials.gov number NCT01169038.